Involvement of transient receptor potential melastatin type 7 channels on Poncirus fructus-induced depolarizations of pacemaking activity in interstitial cells of Cajal from murine small intestine - Kim, Byung Joo (Integr Med Res, 2013)
BACKGROUND: Extracts of Poncirus trifoliata (L.) Raf. (Rutaceae; PT) are widely used as a traditional medicine in Eastern Asia, especially for the treatment of gastrointestinal (GI) disorders related to GI motility. Interstitial cells of Cajal (ICCs) are pacemakers in the GI tract, and transient receptor potential melastatin type 7 (TRPM7) channels and Ca(2+) activated Cl(–) channels are candidate pacemaker channels. METHODS: In the present study, the effects of a methanolic extract of the dried roots of PT on ICC pacemaking activity were examined using the whole-cell patch-clamp technique. RESULTS: The methanolic extract of PT (PTE) was found to decrease the amplitudes of pacemaker potentials in ICC clusters and to depolarize the resting membrane potentials in a concentration-dependent manner. Intracellular GDP-β-S suppressed PTE-induced depolarizations, and pretreatment with a U-73122 (a phospholipase C inhibitor) or with 2-APB (an 1,4,5-inositol triphosphate receptor inhibitor) abolished this generation of pacemaker potentials and suppressed PTE-induced effects. The applications of flufenamic acid, niflumic acid, waixenicin A, or 5-lipoxygenase inhibitors (NDGA or AA861) abolished this generation of pacemaker potentials and inhibited PTE-induced membrane depolarization. Furthermore, PTE inhibited TRPM7 channels but did not affect Ca(2+)-activated Cl(–) channels (both channels play important roles in the modulation of the pacemaking activity related to GI motility). CONCLUSION: These results suggest that the PTE-induced depolarization of pacemaking activity occurs in a G-protein-, phospholipase C-, and 1,4,5-inositol triphosphate-dependent manner via TRPM7 channels in cultured ICCs from murine small intestine, which indicates that ICCs are PTE targets and that their interactions affect intestinal motility.